Kajian Metode Sosiodrama Dalam Meningkatkan Keaktifan Belajar Peserta Didik di Sekolah Dasar - Ismah Ismah; Yunika Afryaningsih; Suriyana Universitas (Jurnal Pendidikan Indonesia (JOUPI), 2024)
This research aims to analyze the steps for using the sociodrama method to increase students’ active learning in elementary school. This research is based on low learning activity, students tend to be quiet and lack enthusiasm during the learning process. Therefore, the importance of learning methods that are interesting and not boring. This research focuses on the steps of the sociodrama method which include 1) determining the theme, 2) determining the role/actor, 3) preparing the role, 4) preparing the audience (observer), 5) implementing sociodrama, and 6) Follow up. This research method uses descriptive qualitative research with a library study type. The data collection technique uses documentation with primary data sources in the form of 20 articles. The results of this research found that there were 13 articles that explained the steps of the sociodrama method and 7 other articles did not explain the steps of the sociodrama method. Based on this analysis, researchers found that the sociodrama method was able to increase students’ active learning. Apart from that, the application of the sociodrama method is also very effective in improving speaking skills, honing students’ creativity, fostering a spirit of solidarity and fostering cooperation between students.